Atomically precise thiolate‐protected gold nanoclusters: Current status of designability of the structure and physicochemical properties. Issue 2 (30th July 2022) - Hossain, Sakiat; Hirayama, Daisuke; Ikeda, Ayaka; Ishimi, Mai; Funaki, Sota; Samanta, Arpan; Kawawaki, Tokuhisa; Negishi, Yuichi
Abstract: Thiolate (SR)‐protected gold nanoclusters (Au n (SR) m NCs) are a rare type of material capable of simultaneously exhibiting multiple physicochemical properties well‐suited to specific applications, including photoluminescence, thermocatalysis, electrocatalysis, photocatalysis, magnetism, and optical activity. Over the past several decades, there has been tremendous progress in our understanding of the structure and physicochemical properties of Au n (SR) m NCs, resulting in the ability to fine‐tune the characteristics of these materials. It is therefore helpful to examine the extent to which the properties of Au n (SR) m and related metal NCs can now be adjusted based on design. This review presents representative examples of previous studies concerning the geometry, electronic structure, luminescence properties, catalysis, magnetism and optical activity of Au n (SR) m and related metal NCs and discusses the current status of the designability of these NCs to impart specific structural and physicochemical characteristics. This information is expected to accelerate the fabrication of highly functional materials based on Au n (SR) m and related metal NCs. Abstract : This review presents representative examples of previous studies concerning the geometry, electronic structure, luminescence properties, catalysis, magnetism, and optical activity of thiolate‐protected gold nanoclusters (Au n (SR) m NCs) and related metal NCs and discusses the current status of the designability of these NCs to impart specific structural and physicochemical characteristics. This information is expected to accelerate the fabrication of highly functional materials based on Au n (SR) m and related metal NCs.